Acid-corrosion-formed amorphous phosphate surfaces improve electrochemical stability of LiNi0.80Co0.15Al0.05O2 cathodes. (15th May 2020) - Zhao, Shuangshuang; Shao, Li; Li, Xiang; Yang, Lishan; Wei, Bin; Yang, Yahui; Zhao, Haihong; Yin, Dulin; Ma, Wenqing; Wang, Zhongchang
Graphical abstract: Highlights: Amorphous phosphate layers are formed directly at surface of LiNi0.80 Co0.15 Al0.05 O2 (NCA) particles from a H3 PO4 -ethanol solution. The phosphate coated NCA materials exhibit prominent electrochemical performance and stability as a cathode for lithium-ion batteries. The phosphate coated NCA cathode shows a capacity retention of 68.8 % after 300 cycles in 3.0–4.5 V and 5C-rate. Abstract: We report a surface modification of LiNi0.8 Co0.15 Al0.05 O2 (NCA) materials with a phosphate layer via a room-temperature corrosion approach from H3 PO4 -ethanol solution. The phosphate layer is of amorphous nature with a thickness of 2∼3 nm, and consequently, NCA maintains its bulk structure during cycling and possesses significantly enhanced rate property of 153.7 mA h g −1 at 5C. Simultaneously, such a modified system demonstrates an excellent cycling stability (107.5 mA h g −1 ) and coulombic efficiency (>90 %) after 300 cycles at 5C. The findings highlight that the acid corrosion treatment represents a facile and efficient way in developing advanced NCA cathodes.